The rise and fall of the middle class: technology, skills, and inequality - Rivera, L (2016)
Over the twentieth century advanced economies have seen an economic and social development process which was build upon the consolidation of a strong middle class. Yet, recent decades have seen an increase in wealth and income inequality, reaching levels not seen since before the Second World War. This thesis explore some of the these issues in two parts. The focus of the first part of the thesis is on the role of education and technology in the rise of the middle class. By means of an overlapping generations model with endogenous growth, I study the conditions that enable a society to transit from underdevelopment to development. The model in place reproduces a Kuznets curve, which is deemed an important empirical feature of the history of advanced economies. The second part focuses on the fall of the middle class, by studying the effect of technology and skills in job polarisation – i.e. the fall in employment in middle-skill occupations. The approach is both theoretical and empirical. A sorting model based on tasks is developed and adapted to study polarisation. Central to this model are the distributions of skills that workers have. Thus, a complete chapter is dedicated to characterise these ability distributions, using longitudinal data from the UK for 1991-2008 in an econometric model based on the so-called Mincer equation. The estimated distributions – positive skewed – are used to calibrate the sorting model. Then, this model is used to identify the nature of the technological process affecting the UK economy over the selected period of study. Simple counterfactual exercises shed light on the strong effect of technical progress on both polarisation and inequality. In contrast, the role of change in skills is negligible. The overall conclusion is that the nature of technological change is essential in defining distributional outcomes: whilst technology can enable the rise to a strong middle class, it can also undermine it.